Kapasistas Organisasi Lokal dalam Sertifikasi Hutan di Kabupaten Gunungkidul - SULISTYANINGSIH SULISTYANINGSIH (Jurnal Studi Pemerintahan, 2010)
The existence of people forest in Java was marginalized for a long time has changed. It was happenedafter state deforestation in Java. It can be shown by people forest in Gunung KidulDistrict,Yogyakarta. The people forest has gotten sertification strenghten the legitimation of realpeople role in forest management. In this context is needed local institution strenghten. The stronglocal institution is hoped to become social capital for community in people forest management . Itmakes farmers of people forest have strong and high bargaining posistion toward marketintervention. But, in this case, state role in market intervention become important factor too. Statemust give protection toward the farmers of people forest.